PENTINGNYA KOMPETENSI MULTIKULTURAL BAGI KONSELOR DALAM MENGHADAPI KEBERAGAMAN BUDAYA - Elviana Rohmah Rosyidatul 'Ula; Aradhana Maheswara; Azizah, Taqiyyatul; Nailah Lubis, Shabrina; Khusumadewi, Ari; Nur Fadilah, Ela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cultural diversity is a fundamental characteristic of Indonesian society that influences various aspects of life, including guidance and counseling services. Differences in cultural backgrounds, values, norms, and individual perspectives can affect the counseling process, both in understanding problems and determining appropriate intervention strategies. Therefore, counselors are required to possess multicultural competence in order to provide effective and responsive services to clients’ needs. This article aims to examine the importance of multicultural competence for counselors in dealing with cultural diversity. The method used in this study is a literature review by analyzing various scientific sources related to multicultural counseling. The results indicate that multicultural competence consists of three main components, namely self-awareness, knowledge, and skills, which are interrelated in supporting the effectiveness of the counseling process. In addition, this competence plays an important role in minimizing cultural bias, improving the quality of the counseling relationship, and helping counselors understand clients more comprehensively. Thus, multicultural competence becomes an essential aspect that must be possessed by counselors to create inclusive and effective counseling services in a diverse society.